PROSES OPERATIONS READINESS PT MARUWAI COAL - Erwin Tampubolon; Saladin Ghalib; Jamaluddin Jamaluddin (Universitas Lambung Mangkurat, 2021)
There is a risk that the transition process from the mining construction stage to the mining production operation stage will fail, which will have an impact on the production operation going forward. The impact of productivity, cost, social and security, commitment to customers are concerns. This study aims to find out what happened during the transition phase of construction to mining production operations at PT Maruwai Coal.To achieve these objectives this research uses a qualitative approach, case studies, data collection by interviews, observations and documentation and directly involved in the Operations Readiness process.The steps to create an Operations Readiness Plan and an Operations Readiness Execution Plan are critical in determining the success of Operations Readiness, which focuses on building a team, licensing and community acceptance, building infrastructure and mapping operational needs and schedules.Thus Operation Readiness requires a schedule, budget, organizational structure and senior management commitment. Operations Readiness must be considered for implementation by mining companies in preparing new mining operations from the start.Keywords: Operations Readiness, PT Maruwai Coal